Colorectal Cancer Metastasis of and the Risk Factors - Ahmad Soefyani; Abdul Aziz Rani; Marcellus Simadibrata; Murdani Abdullah; Ening Krisnuhoni (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Colorectal cancer (CRC) is the fourth most prevalent cancer in the world and is positioned the second most common cancer in the United States. Patients with CRC in Indonesia showed a greater proportion. In Jakarta, 47.85% of CRC cases occur under the age of 45 years. The purpose of this study is to determine metastasis and the factors that influence colorectal cancer patients. Method: This study was conducted retrospectively from January 2003-December 2007 in Cipto Mangunkusumo hospital. Patients are eligible if they underwent colonoscopy, tumor biopsy, anatomical pathology, abdominal CT scan, abdominal ultrasonography, and radiology procedures. Result: Of all 1,615 patients who underwent colonoscopy procedure, 377 patients were diagnosed with colorectal cancer. Subject that met the criteria consist of 86 patients, where 56 (65.1%) male. Most aged 51-60 years old (26.7%), mean age 47.90 ± 14.53 years old. The tumor is most commonly located in the rectum and sigmoid 40 (46.5%), in which 18 (45%) among them had metastasized. Compared with male patients, female patients experienced more metastases, but not statistically significant. Among the patients with metastasized CRC, 42.3% of them 40 years old, 37.2% patients 41-60 years old, and 29.4% patients 60 years old. Well-differentiated CRC produce larger number of metastatic cases than poorly-differentiated CRC. Poorly-differentiated CRC tend to produce adjacent metastasis, and also happened in relatively young age in compared with well-differentiated cancer. Conclusion: There was significant correlation between younger age group with a poor degree of histopathologic differentiation. Patients with CRC consist of more male patients than female ones. Factors sex, age group, histopathologic subtypes, and tumor location was not associated with metastasis. Keywords: colorectal cancer, metastasis, well-differentiated, poorly-differentiated